Parental knowledge and attitudes toward providing sex education to children with down syndrome in Indonesia: A Cross-sectional study - Nur Indriasari, Fika; Daniyati Kusuma, Prima (Jurnal Keperawatan, 2026)
Introduction: Children with Down syndrome are more vulnerable to sexual abuse because of cognitive limitations, dependence on caregivers, and difficulty identifying inappropriate behavior. Early, developmentally appropriate sex education is therefore important as a preventive measure. Parents, as primary educators, play a central role, though their sociodemographic backgrounds, knowledge, and attitudes may affect how sex education is delivered.Objectives: This study examined the relationships between parents’ age, gender, education level, and knowledge with parental attitudes toward providing sex education to children with Down syndrome in Indonesia.Methods: A cross-sectional correlational design was used with 32 parents of children with Down syndrome selected through purposive sampling. Data were collected using structured questionnaires on parental knowledge and attitudes toward sex education. Pearson correlation analysis was applied after normality and linearity assumptions were met. Descriptive data were presented as mean ± standard deviation.Results: The mean parental knowledge score was 19.72 ± 2.57 out of 23, indicating a sufficient level. The mean attitude score was 34.75 ± 3.72, indicating a moderate attitude. Parental knowledge showed a significant small-to-moderate positive correlation with attitudes toward providing sex education (r = 0.357, p = 0.045). In contrast, age, gender, and education level were not significantly associated with parental attitudes.Conclusions: Greater parental knowledge was associated with more positive attitudes toward sex education for children with Down syndrome. Improving parental knowledge through structured, culturally appropriate education and nursing-based counseling may strengthen preventive efforts against sexual violence.